Risk factors for early weaning - Margotti, Edficher; Mattiello, Rita (Rev Rene, 2016)
Objective: to determine the risk factors for early weaning. Methods: cohort study with 300 mothers/babies couples, carried out in two hospitals. The Edinburgh Scale was used to verify the existence of depressive tendencies in mothers with four months babies. Results: the risk factors for exclusive breastfeeding at 2 and 3 months were the score of Edinburgh (p=0.048 and p=0.000), not Child-Friendly Hospital (p=0.002 and p=0.001) and mother working outside the home (p=0.013 and p=0.007). Maternal education was a risk factor only at 2 months (p=0.004). There 38.0% of mothers with depressive tendency with their children hospitalized in the not Child-Friendly Hospital. Conclusion: not Child-Friendly Hospital, a mother who works outside the home and score Edinburgh proved as risk factors for exclusive breastfeeding at 2 and 3 months of baby´s life, and women with depressive tendencies had a predisposition to weaning.